Peran Mahasiswa dalam Meningkatkan Wirausaha Muda : Studi Kasus STIE Ganesha - Ekky Noviar; Fisy Amalia; Tetty Nur Intan Rifia; Afandi Rachman; Adi Wicaksono (Jurnal Visi Manajemen, 2024)
This study is motivated by the importance of the role of students in promoting and enhancing young entrepreneurs in Indonesia, particularly within higher education environments. Students, with their creativity and spirit of innovation, have great potential to become agents of change in developing the entrepreneurial sector. The purpose of this study is to identify the role of STIE Ganesha students in supporting the growth of young entrepreneurs, examine factors influencing entrepreneurial success, and evaluate the impact of entrepreneurship programs at STIE Ganesha. This research employs a case study method with a qualitative approach. Data were collected through in-depth interviews and questionnaires distributed to 100 students actively participating in entrepreneurship programs at STIE Ganesha. The study was conducted over three months, from June to August 2024. The research subjects are students involved in campus entrepreneurship activities. The results indicate that students play a significant role in enhancing young entrepreneurship through business initiatives, participation in entrepreneurship training, and support from campus business incubators. Factors such as institutional support, access to capital, and business networks are critical determinants of entrepreneurial success. This study recommends strengthening entrepreneurship programs at STIE Ganesha with supportive policies, improved facilities, and broader access to business resources. These findings are expected to serve as a reference for educational institutions and the government in supporting the development of young entrepreneurs in Indonesia.